Genome-wide Analysis of DNA Methylation Variations Caused by Chronic Glucolipotoxicity in Beta-Cells - Hu, Y.; Xu, X.-H.; He, K.; Zhang, L.-L.; Wang, S.-K.; Pan, Y.-Q.; He, B.-S.; Feng, T.-T.; Mao, X.-M. (Experimental and Clinical Endocrinology & Diabetes, 2014)
There is a growing body of literature suggesting the role of interactions between genes and the environment in development of type 2 diabetes mellitus (T2DM). However, the interplay between environment and genetic in developing and progressing T2MD is not fully understood. To determine the effects of high-glucose-lipid on the status of DNA methylation in beta cells, and clarify the mechanism of glucolipotoxicity on beta-cell deterioration, the DNA methylation profile was detected in beta-cells cultured with high-glucose-lipid medium.We utilized a high throughput NimbleGen RN34 CpG Island & Promoter Microarray to investigate the DNA methylation profile in beta-cells cultured with high-glucose-lipid medium. To validate the results of microarray, the immunoprecipitation (MeDIP) PCR was used to test the methylation status of some selected genes. The mRNA and protein expression of insulin and Tcf7l2 in these cells were quantified by RT-PCR and western blot, respectively.We have identified a lot of loci which experienced aberrant DNA methylation in beta-cells cultured with high-glucose-lipid medium. The results of MeDIP PCR were consistency to the microarray. An opposite regulation in transcription and translation of Tcf7l2 gene was found. Furthermore, the insulin mRNA and protein expression in beta-cells also decreased after cultured with high-glucose-lipid medium compared with the control cells.We conclude that chronic glucolipotoxicity could induce aberrant DNA methylation of some genes and may affect these genes expression in beta-cells, which might contribute to beta-cell function failure in T2DM and be helpful to explain, at least partially, the mechanism of glucolipotoxicity on beta-cells deterioration.
Keywords: type 2 diabetes; DNA methylation; glucolipotoxicity; beta-cells; genome-wide analysis